Novel Role for Matrix Metalloproteinase 9 in Modulation of Cholesterol Metabolism. Issue 10 (October 2016) - Hernandez‐Anzaldo, Samuel; Brglez, Vesna; Hemmeryckx, Bianca; Leung, Dickson; Filep, Janos G.; Vance, Jean E.; Vance, Dennis E.; Kassiri, Zamaneh; Lijnen, Roger H.; Lambeau, Gérard; Fernandez‐Patron, Carlos
Abstract : Background: The development of atherosclerosis is strongly linked to disorders of cholesterol metabolism. Matrix metalloproteinases (MMPs) are dysregulated in patients and animal models with atherosclerosis. Whether systemic MMP activity influences cholesterol metabolism is unknown. Methods and Results: We examined MMP‐9–deficient ( Mmp9 −/− ) mice and found them to have abnormal lipid gene transcriptional responses to dietary cholesterol supplementation. As opposed to Mmp9 +/+ (wild‐type) mice, Mmp9 −/− mice failed to decrease the hepatic expression of sterol regulatory element binding protein 2 pathway genes, which control hepatic cholesterol biosynthesis and uptake. Furthermore, Mmp9 −/− mice failed to increase the expression of genes encoding the rate‐limiting enzymes in biliary cholesterol excretion (eg, Cyp7a and Cyp27a ). In contrast, MMP‐9 deficiency did not impair intestinal cholesterol absorption, as shown by the 14 C‐cholesterol and 3 H‐sitostanol absorption assay. Similar to our earlier study on Mmp2 −/− mice, we observed that Mmp9 −/− mice had elevated plasma secreted phospholipase A2 activity. Pharmacological inhibition of systemic circulating secreted phospholipase A2 activity (with varespladib) partially normalized the hepatic transcriptional responses to dietary cholesterol in Mmp9 −/− mice. Functional studies with mice deficient in other MMPs suggested an important role for the MMP system, as a whole, in modulation of cholesterol metabolism. Conclusions: Our results show that MMP‐9 modulates cholesterol metabolism, at least in part, through a novel MMP‐9–plasma secreted phospholipase A2 axis that affects the hepatic transcriptional responses to dietary cholesterol. Furthermore, the data suggest that dysregulation of the MMP system can result in metabolic disorder, which could lead to atherosclerosis and coronary heart disease.